Island-sensitivity of two different interpretations of why in Chinese - Kim, Nayoun; Li, Ziying; Lu, Jiayi (Frontiers in Psychology, 2023)
It has been assumed that the wh-element weishenme “why” in Chinese has two distinct interpretations: a reason reading, which typically yields yinwei “because”-answers, and a purpose reading, which typically triggers weile “in order to”-answers. It is claimed that the two interpretations differ in island sensitivity: the reason weishenme is sensitive to islands while the purpose weishenme is not. Assuming that the reason weishenme is a wh-adverb without finer internal structure, while the purpose weishenme is a wh-PP consisting of the preposition wei “for” and a wh-DP shenme “what,” this contrast in island sensitivity can be considered as an instance of a broader generalization: the so-called argument-adjunct asymmetry (or the DP-adverb asymmetry) of wh-in-situ island sensitivity. However, recent experimental studies provided mixed findings on whether the argument-adjunct asymmetry of wh-in-situ island sensitivity actually holds. The current study focuses on the two interpretations of weishenme “why/for what” in Chinese, and provides evidence using a formal acceptability judgment experiment that the two weishenmes are both sensitive to islands, contrary to previous generalizations. Our results provide further empirical challenge to the so-called argument-adjunct asymmetry of wh-in-situ island sensitivity.